The psychometric properties of parenting styles and dimensions questionnaire-short form in Indonesia - Anayanti Rahmawati; Fajrianthi Fajrianthi; Urip Purwono (International Journal of Evaluation and Research in Education (IJERE), 2022)
Parenting style was a set of parental attitude and behavior communicated by parents to children, forming an emotional climate condition used by parents to raise children. The study on parenting style had been conducted for a long time, but measurement of parenting style in Indonesia was still experiencing problem due to lack of sufficient and proper instrument, despite the monumental need for a valid and reliable instrument. The aim of this study was to examine the factor structure, internal consistency and others psychometric properties of the Indonesian version of the parenting styles and dimensions questionnaire-short form (PSDQ-SF). The instrument comprises 32 items (12 questions regarding the authoritative style, 15 questions regarding the authoritarian style, and five questions regarding the permissive style). The research sample consisted of 169 mothers with children of 5-7 years of age. Research was conducted in Sukoharjo, Central Java, Indonesia. Structural equation modelling (SEM) with LISREL 9.20 was utilized as the data analysis technique. Data analysis results by CFA second order showed that construct validity testing fulfilled the minimum criteria, with the factor loading range of 0.51-0.99. The reliability score’s Cronbach’s alpha also fulfilled the requirement, including the authoritative parenting style 0.86; the authoritarian parenting style 0.76 and the permissive authoritarian parenting style 0.67. These findings support the PSDQ-SF original structure. The results showed that the adaptation of PSDQ-SF in Indonesia was valid and reliable to use in measurement of parenting styles of parents of children of 5-7 years of age in Indonesia.